HUBUNGAN KESEGARAN JASMANI DENGAN HASIL BELAJAR SISWA KELAS XI IPS SEKOLAH MENEGAH ATAS PEKANBARU - ', Adrian; ', Slamet; ', Zainur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Â Abstract: Problem in this research starts from writer observation found in the field that the achievement of learning outcomes almest of student still relatively low. It is proved by odd mid smester examination score in school year 2013/2014 still below average or below minimum completeness criteria(KKM)score so that many student who did not complete in many subjects.purpose of this research is to understand the corelation between physical fitness with students learning achievement at social class in pekanbaru senior high school kind of this research is male students at social class in pekanbaru senior high school number in 20 person are using for total sampling technique which is all the population be created as sample then sample of this research is 20 person. to get research data, it used Indonesia(TKJI) pyscal fitness test and the result of the smester report card.the data obtain were analyzed by simple correlation of product moment. based on result of the research which has writer expalain in previous bab, so it can get the conclution that there is no corelation between psycal fitness with students learning achievement at XI social class in pekanbaru senior high school,it marked by rhitung(0,034)<rtabel(0,456). Â Keyword: Physical fitness,learning achievement.